The Influence Of Counseling With Abpk And Wheel Klop On Participation In Post Party Kb In The Muncak Health Center Oku Kabau East South Sumatra - Umita Sofyana; Rahmadyanti Rahmadyanti (CV. Inara, 2024)
Background: Counseling with dual role health workers (ABPK) and the application of the clutch wheel method can have a significant positive impact on participation in postnatal family planning (KB) programs. Purpose of writing: to determine the effect of ABPK and Rodak Lop counseling on postpartum family planning participation at the Muncak Kabau Oku East Community Health Center, South Sumatra in 2023 Research Method: The method in this research is experimental with a Pretest Posttest type of research without a control group. Statistical test data processing uses a paired sample t test if the normality test is normally distributed, if it is not normally distributed using the Wilcoxon test carried out univariately and bivariately with the help of the SPSS 25.0 computer program. Research Results The research results are known as Asymp. Sig (2 – Talled) has a value of 0.000 because 0.000 < 0.05, it can be concluded that the hypothesis is accepted. This means that there is an influence of counseling with ABPK and Roda Klop on postpartum family planning participation at the Muncak Kabau Oku East Community Health Center, South Sumatra in 2023 Conclusions and Suggestions: Health workers, especially midwives, can use ABPK and the klop wheel as a means of providing counseling so that it can make it easier for family planning acceptors to make contraceptive choices.